Facts about Wildlife Diseases: Rabies - Samantha M. Wisely; Holly K. Ober (EDIS)
Rabies is a virus carried by mammals. It kills infected humans and animals if they are not treated shortly after exposure. Rabies can be prevented, but it cannot be cured once symptoms become evident. This revised 6-page fact sheet explains how rabies spreads, which animals can get it, how common it is, symptoms, what you can do to limit its spread and what to do in case of a possible rabies exposure. Written by Samantha M. Wisely and Holly K. Ober, and published by the UF Department of Wildlife Ecology and Conservation, June 2015.